Breaking into Tradables: Urban Form and Urban Function in a Developing City - Venables, A (World Bank eLibrary, 2017)
Many cities in developing economies, particularly in Africa, are experiencing urbanization without industrialization. This paper conceptualizes this in a framework in which a city can produce non-tradable goods and—if it is sufficiently competitive—also internationally tradable goods, potentially subject to increasing returns to scale. A city is unlikely to produce tradables if it faces high urban and hinterland demand for non-tradables, or high costs of urban infrastructure and construction. The paper shows that, if there are increasing returns in tradable production, there may be multiple equilibria. The same initial conditions can support dichotomous outcomes, with cities either in a low-level (non-tradable only) equilibrium, or diversified in tradable and non-tradable production. The paper demonstrates the importance of history and expectations in determining outcomes. Essentially, a city can be built in a manner that makes it difficult to attract tradable production. This situation might be a consequence of low (and self-fulfilling) expectations or history. The predictions of the model are consistent with several observed features of African cities.